Fraught with Tension: The Question of the Unity of the Corpus Dionysiacum - Stock, Wiebke-Marie (Journal of early Christian studies, 2024)
There is debate about whether the Corpus Dionysiacum consists of two parts or offers a coherent position. One group of scholars presents a divisionist position, distinguishing one group of treatises dominated by the idea of hierarchical mediation from a second concentrating on the idea of individual and mystical knowledge of God. The second scholarly interpretation supports a holistic view and underlines the unity of the Corpus. I argue that the Corpus is a unity fraught with tension. Dionysius presents, I argue, a comprehensive view of human beings and their place in the world that offers different—and maybe at times competing—paths to understanding and to the ascent to the divine. The mystical, metaphysical, and meditative path and the sacramental path are not merely parallel ways, one for monks and the other for the bishops and laity. They are connected through the communal theological work presented in the fiction of a theological correspondence between the author and various members of the hierarchy.